488. SARS-CoV-2 Preparedness among Community Hospitals in Southeastern United States. (31st December 2020) - Advani, Sonali D; Baker, Esther; Cromer, Andrea; Wood, Brittain A; Crawford, Kathryn; Crane, Linda S; Adcock, Linda; Roach, Linda; Padgette, Polly W; Anderson, Deverick J; Sexton, Daniel
Abstract: Background: The SARS-CoV-2 pandemic has placed a tremendous strain on the U.S. healthcare system leading to personal protective equipment (PPE) and resource shortages. Hospitals have developed contingency and crisis capacity strategies to optimize the use of resources, but, to date, community hospital preparedness has not been described. Methods: We performed a cross-sectional survey of infection preventionists in 60 community hospitals within the Duke Infection Control Outreach Network between April 22 and May 7, 2020 using Qualtrics. The survey included 13 questions related to resource availability, crisis capacity strategies and approaches to testing. Results: We received 50 responses during the study period with a response rate of 83%. Community hospitals reported varying degrees of PPE shortages (Table 1); 80% of community hospitals were implementing strategies to extend and reuse N95 respirators, Powered Air-Purifying Respirators, face shields and face masks. Over 70% of facilities reported reprocessing N95 respirators (Figure 1). Almost all facilities reported universal masking at time of this survey with 90% performing daily employee screening at point of entry. Additionally, 8% of facilities restarted elective procedures at the time of this survey, but only 54% of facilities reported that they were performing preoperative testing for SARS-CoV-2. Thirty-seven percent of facilities performed one SARS-CoV-2 test before discharging an asymptomatic patient to skilled nursing facility, while 43% of facilities performed 2 tests. Table 1- Supply of Personal Protective Equipment and other resources in 50 community hospitals in southeastern United States Figure 1: Different methods of reprocessing N95 respirators by 50 community hospitals in southeastern United States Conclusion: Our findings reveal differences in resource availability, crisis capacity strategies and testing approaches used by community hospitals in preparation for the SARS-COV-2 pandemic. Lack of harmonization in approaches may be in part due to differences in state guidelines and decentralized federal approach to SARS-CoV-2 preparedness. Disclosures: All Authors : No reported disclosures